Dimensi Sosial Masyarakat dalam Praktik Literasi pada Anak (Studi Kasus Taman Bacaan Masyarakat Posko Ilmu Kota Padang) - Ikhsan, Risky Jumatul; Primadesi, Yona (Departemen Informasi Perpustakaan dan Kearasipan, 2023)
This research aims to describe the socio-cultural dimensions of literacy practice in children at the Taman Bacaan Masyarakat Posko Ilmu Kota Padang. This research was using a descriptive qualitative method. Snowball sampling was used as the technique for determining informants, which is determining informants from a few to a lot according to directions from previous informants for the needs of researchers in providing complete and accurate information. Data collection techniques were carried out by interview, observation, and documentation methods. This study uses source triangulation. The results of this study indicate that (1) the family environment in literacy practice at the Taman Bacaan Masyarakat Posko Ilmu Kota Padang influences literacy practices carried out by children caused by the way parents educate their children, family economic conditions, and parents' attention, (2 ) the community environment in literacy practices at the Taman Bacaan Masyarakat Posko Ilmu Kota Padang influences literacy practices carried out by children caused by children's activities in the community, social friends, mass media, and forms of community life.